Events that occur in premature babies before death during their hospital stay - Akhter, Rowshan Jahan; Chowdhury, Kanta; Jahan, Nishat; Hoque, M. Mahbubul (International Journal of Contemporary Pediatrics, 2023)
Background: Globally, more than 80% of newborn babies die due to LBW. PT/LBW babies usually die because of complications from prematurity rather than the prematurity itself. Due to prematurity, they face several problems during their early life, like temperature control, feeding problem, poor immunity, respiratory insufficiency etc. and especially during SCANU and NICU stay they develop sepsis, NEC leading to their death. The aim of this study was to find out the events that occur before the death of premature neonates admitted in the NICU. Methods: A retrospective study conducted in the NICU of Department of neonatology of Bangladesh Shishu Hospital and Institute, Dhaka, Bangladesh during the period from January, 2021 to December, 2021. During this period preterm babies who died were analyzed. Result: During study period total 95 preterm babies died. Their mean± SD of birth weight was 1228.26±115.60. Majority (40%) of neonates were 28-31 weeks old and majority (59%) neonates were male. We found 27.3% had PNA, 12% had PDA, 19% had RDS and 33.6% had only prematurity during admissions. Among all neonates, 51.58% developed sepsis, 40% pneumonia, 34% pulmonary hemorrhage 20% intra ventricular hemorrhage, 25% NEC, 13.6% BPD and 12% PDA respectively and finally died. Conclusion: In our study, 32 (33.6%) babies admitted with only prematurity and rest were admitted with other diagnosis like PNA (27.3%), RDS (19%,) PDA (12%) and CHD (9.4%). However, they finally died of Sepsis 49 (51%), Pneumonia 38 (40%), IVH 19 (20%), NEC 24 (25.2%), BPD 13 (13.6%), Pulmonary Hemorrhage 33 (34.7%).